A reciprocating compressor hybrid model with acoustic FEM characterization. (March 2016) - Stiaccini, Isacco; Galoppi, Giovanni; Ferrari, Lorenzo; Ferrara, Giovanni
Highlights: A time-frequency hybrid model is developed for the analysis of reciprocating compressors. A procedure based on acoustic FEM simulation results is used for the compressor plenum characterization. A CO2 reciprocating compressor for refrigeration applications is numerically and experimentally tested. The comparison between the numerical results and experimental data highlights the reliability of the hybrid model. The hybrid model with acoustic FEM gives more detailed results respect to the hybrid model with acoustic lumped elements. Graphical Abstract: Abstract: In order to analyze the thermodynamic and acoustic performance of a compressor for refrigerating applications, the authors developed a hybrid numerical model that allows to carry out simultaneously the time-domain analysis of the compressor thermodynamic cycle and the frequency-domain acoustic analysis of the pipelines system. An acoustic characterization method based on acoustic FEM simulation results was also defined to model in detail the compressor cavities with complex geometries (i.e. compressor plena). The results of the compressor hybrid model with both acoustic FEM characterization and acoustic lumped elements were compared with experimental measurements. Moreover, a comparison between the developed hybrid model and the stand-alone compressor model with constant pressure boundary conditions was carried out. The advantages in using the acoustic FEM characterization of the complex geometry elements were highlighted.